Pregnant Populations which Benefit from Vaginal Progesterone for Preventing Preterm Birth at <34 Weeks and Neonatal Morbidities: A Systematic Review and Meta-analysis - Lin, Xiaobin; Nie, Yu (American Journal of Perinatology, 2022)
This study aimed to assess vaginal progesterone's effect on different populations and performed comparation between women with varied risk factors. Embase, PubMed, Cochrane library (CENTRAL) were searched without restriction to language up to February 25, 2021. Randomized controlled trials (RCTs) assessing vaginal progesterone administered to women at risk of preterm birth at <37 weeks. Two reviewers independently extracted data, and pooled relative risk (RR) with 95% confidence intervals (CIs) was calculated as well. Women with short cervix have a significantly lower risk of preterm birth at <34 weeks (pooled RR = 0.65; 95% CI: 0.55–0.77; I2 = 0; p < 0.001; nine studies) and some neonatal morbidities; interaction tests showed that effect of vaginal progesterone differs significantly between women with short cervix and those with other risk factors (history of preterm birth, exclusive twin gestation, and vaginal bleeding). Evidences of this study showed that singleton gestations, as well as women with short cervix, benefit from vaginal progesterone in preventing preterm birth at <34 weeks and some neonatal morbidities. Women with short cervix are populations who benefit the most among other risk populations.Key Points
Keywords: neonatal morbidity; preterm birth; risk factors; short cervix; vaginal progesterone